2003
DOI: 10.1088/0022-3727/36/24/012
|View full text |Cite
|
Sign up to set email alerts
|

Pyroelectric properties of phosphoric acid-doped TGS single crystals

Abstract: Pyroelectric properties of phosphoric acid (H3PO4)-doped triglycine sulfate (TGSP) single crystals grown from solutions containing 0.1–0.5 mol of H3PO4 have been studied. Incorporation of H3PO4 into the crystal lattice is found to induce an internal bias field (Eb) and is observed through the presence of a sustained polarization and pyroelectricity beyond the transition temperature. The internal bias field has been estimated theoretically by fitting the experimentally measured data on temperature dependence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…4 the hysteresis loop in doped samples has a double form. This can be a consequence of the PO 3− 4 ions [11]. ¿From the hysteresis loop on the screen and Eqs.…”
Section: P-e Hysteresis Loopmentioning
confidence: 99%
“…4 the hysteresis loop in doped samples has a double form. This can be a consequence of the PO 3− 4 ions [11]. ¿From the hysteresis loop on the screen and Eqs.…”
Section: P-e Hysteresis Loopmentioning
confidence: 99%
“…It is obtained by partial substitution of sulphate ions with phosphate ions in TGS crystal and this partial substitution phosphate ions delays microbial contamination during the growth and avoids depolarization with time [2,3]. Aparna Saxena et al reported the various characterization studies on phosphoric acid doped TGS (TGSP) crystals and observed that the dielectric constant of TGSP crystal is low as that of TGS crystal and hence increases the pyroelectric figure of merit [4,5]. Doping crystals with various kinds of dopants influences the solubility, growth rate, morphology, structural, electrical and other properties of the crystals [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] TGS crystals show second-order phase transitions from the monoclinic space group P2 1 (ferroelectric phase) to the monoclinic space group P2 1 =m (para electric phase) at a Curie temperature of 49 C. 4) Phosphoric acid substituted TGS (TGSP) crystals have also been widely studied for use in ferroelectric and pyroelectric devices. 5,6) We have studied (1 À x)Pb(Mg 1=3 Nb 2=3 )O 3 -xPbTiO 3 (PMN-PT) ceramics with composition-controlled multilayers (x ¼ 0 to 0.24 step 0.02), and these samples showed a flat dielectric curve with high dielectric constants from room temperature (RT) to 120 C. 7) These materials are called ''functionally graded materials (FGMs)''. Using such materials, it is possible to design a FGM capacitor with high and flat dielectric profiles as a function of temperature by controlling the composition of the ferroelectrics.…”
Section: Introductionmentioning
confidence: 99%